2006
DOI: 10.1074/jbc.m600137200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Mouse Peptide N-Glycanase-HR23 Complex Suggests Co-evolution of the Endoplasmic Reticulum-associated Degradation and DNA Repair Pathways

Abstract: Peptide N-glycanase removes N-linked oligosaccharides from misfolded glycoproteins as part of the endoplasmic reticulum-associated degradation pathway. This process involves the formation of a tight complex of peptide N-glycanase with Rad23 in yeast and the orthologous HR23 proteins in mammals. In addition to its function in endoplasmic reticulum-associated degradation, HR23 is also involved in DNA repair, where it plays an important role in damage recognition in complex with the xeroderma pigmentosum group C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…For comparison, the same ITC experiments were also carried out with yeast PNGase (data not shown). The yeast enzyme neither binds to mannopentaose, which is consistent with the absence of the C-terminal domain in yeast PNGase, nor interacts with chitobiose as one would expect based on the close structural relationship between the core domain of mouse PNGase and full-length yeast PNGase (9,10).…”
Section: The Mouse Pngase C-terminal Domain Binds To Oligomannosementioning
confidence: 48%
See 2 more Smart Citations
“…For comparison, the same ITC experiments were also carried out with yeast PNGase (data not shown). The yeast enzyme neither binds to mannopentaose, which is consistent with the absence of the C-terminal domain in yeast PNGase, nor interacts with chitobiose as one would expect based on the close structural relationship between the core domain of mouse PNGase and full-length yeast PNGase (9,10).…”
Section: The Mouse Pngase C-terminal Domain Binds To Oligomannosementioning
confidence: 48%
“…2C). The oligomannose-binding site is apparently formed by ␤-strands 8, 9, and 16, which provide the concave part of the saddle, and the loops between ␤8 and ␤9, as well as ␤15, ␤16, and the second 3 10 helix, which form the ridges on either side of the saddle. Trp-532 resides in the loop between ␤-strands 8 and 9 and Trp-624 in the 3 10 -2 helix, and these residues are on either side of the binding site.…”
Section: Mannose-binding Site Of the Mouse Pngase C-terminal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse PNGase has N-and C-terminal domains in addition to its central catalytic domain. The N-terminal domain is known to be involved in protein-protein interaction (29), whereas the C-terminal domain may function as a mannose-binding module (30). Allen et al reported that the N-terminal PUB domain of human PNGase consists of five ␣ helices that pack into a short threestranded antiparallel ␤ sheet.…”
Section: Discussionmentioning
confidence: 99%
“…The central region of ubiquilin-1 contains two regions of similarity to the co-chaperone Sti-1 (also known as Hop). Sti-1 domains mediate hydrophobic protein-protein interactions and may possess intrinsic chaperone activity (26,27).…”
mentioning
confidence: 99%